Pengaruh Integritas terhadap Produktivitas Kerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasaman Barat - Yunita Yunita; Syamsir Syamsir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
This study aims to find out and analyze how much influence the level of Integrity has on Employee Work Productivity at the Department of Population and Civil Registration of West Pasaman Regency. The background for conducting this research is because there are still cases found in the field that the productivity of employees at the agency is not yet optimal. One example is that the target of making e-KTP for citizens has not been achieved. If it is percentaged, it is still around 10.75% of the people who have not recorded their e-KTP. This research uses quantitative methods with associative quantitative types. Data was collected by questionnaire and supported by study documentation. Using the Proportionate Stratified Random Sampling technique and using the Slovin formula at a margin of error of 3%, a sample of 60 respondents was obtained. Regression analysis is used to analyze field data, which has previously been tested by classical assumptions. The results showed that integrity proved to have a positive and significant effect on employee productivity by 70.1%.